ANALISIS FAKTOR PENYEBAB PERSALINAN DENGAN SECTIO CAESARIA DI RUMAH SAKIT IBU DAN ANAK CEMPAKA AZ-ZAHRA BANDA ACEH TAHUN 2021-2023 - Sirajul Muna; Suriani; Saumy Rizma (Rena Cipta Mandiri, 2025)
Cesarean section is performed due to specific medical indications, divided into indications for the mother and the baby. However, it has also become an alternative delivery method without medical indications, as it is considered more convenient. Approximately 25% of cesarean deliveries are performed without medical necessity. Data from Cempaka Az-Zahra Mother and Child Hospital shows that cesarean deliveries numbered 130 in 2021, 137 in 2022, and 110 in 2023. This study aims to analyze the factors causing cesarean deliveries at the hospital during 2021–2023. The research used a descriptive retrospective method with a total sample of 377 mothers who delivered via cesarean section, analyzed using univariate analysis with SPSS. Results showed that most mothers were in the non-risk age group (70.6%), multiparous (55.4%), and had term pregnancies (57.6%). The main causes were abnormal fetal position (46.7%) and premature rupture of membranes (35.9%). Conclusion: the dominant factors were non-risk maternal age, multiparity, term pregnancy, abnormal fetal position, and early membrane rupture. It is recommended that health workers improve maternal care with appropriate approaches.